Coexistence of endobronchial aspergilloma, pulmonary embolism, and lung cancer: a case report - Zhu, Chen; Jiang, Zhanshi; Yu, Hui; Gu, Ying (Frontiers in Oncology, 2025)
BackgroundEndobronchial aspergilloma (EBA) represents an uncommon manifestation of pulmonary aspergillosis that may co-occur with other significant respiratory pathologies, notably lung cancer and pulmonary embolism (PE), complicating diagnosis and management.Case presentationAn 83-year-old male with a history of benign prostatic hyperplasia surgery presented with chest pain. Computed tomography angiography (CTA) of the pulmonary arteries revealed both PE and a left hilar mass. Fiberoptic bronchoscopy disclosed a yellow, mushroom-like lesion, with histological examination confirming squamous cell carcinoma. Subsequent bronchoalveolar lavage culture was positive for Aspergillus flavus, confirming the diagnosis of EBA. Despite initiated treatments, the patient declined further therapeutic interventions and succumbed one month following presentation.ConclusionThis case underscores the rare coexistence of EBA, lung cancer, and PE, highlighting considerable diagnostic challenges and the need for integrated multidisciplinary management strategies in such complex presentations.